Changes in metabolic complications in patients with alcoholic fatty liver disease monitored over two decades: NAGALA study - Michiaki Fukui; Masahide Hamaguchi; Yoshitaka Hashimoto; Akihiro Obora; Takao Kojima; Takuro Okamura (BMJ Open Gastroenterology)
Objective The social conditions are changing in the world, which may contribute to the change in lifestyle, including alcohol consumption and dietary intake; however, changes in metabolic complications in patients with alcoholic fatty liver disease (AFLD) have never been reported. Therefore, here we compare the metabolic complications in current AFLD with those of two decades ago.Methods We performed this cross-sectional study in a Japanese health check-up centre. Consecutive participants who visited the facilities between June 1994 and December 1997 or between January 2014 and December 2017 were enrolled. A total of 7499 participants (4804 men, 2695 women) in the past cohort and 20 029 participants (11 676 men, 8353 women) in the current cohort were entered to this study.Results The prevalence of drinkers in the current cohort was significantly lower (4.7%) than that in the past cohort in men (5.9%, p<0.001) but significantly higher in women (1.9% in the current vs 1.1% in the past, p<0.001). The prevalence of fatty liver in drinkers has increased in men (22.3% in the past cohort, 36.6% in the current cohort; p<0.001) but not in women (13.3% in the past cohort, 14.7% in the current cohort; p=1.0), while the prevalence of all fatty liver has increased in men and women (men: 24.0% in the past cohort, 36.2% in the current cohort, p<0.001; women: 9.3% in the past cohort, 12.8% in the current cohort, p<0.001). Regarding metabolic abnormalities, the prevalence of hyperglycaemia increased from 25.4% to 43.0% in men with AFLD (p<0.001) and from 25.1% to 39.1% in women with AFLD (p=1.0).Conclusions AFLD currently tends to be accompanied by hyperglycaemia. The prevalence of fatty liver in drinkers increased in men, although alcoholic consumptions did not increase. We should pay attention to fatty liver combined with hyperglycaemia for individuals who consume alcohol today.